Penerapan Ragam Hias Islami Pada Produk Seni Lukis Desa Jelekong: Strategi Meningkatkan Penjualan Lukisan Di Kalangan Masyarakat Muslim - Agus Cahyana; Asep Miftahul Falah; Martien Roos Nagara (LOSARI DIGITAL, 2026)
This community service program was initiated in response to the limited capacity of painters in Jelekong Village to address the growing demand of the Muslim market for artworks that reflect Islamic values. The program focused on the application of Islamic decorative motifs as a strategy for product innovation and sales enhancement. The objective of this program was to improve the painters’ skills in incorporating Islamic decorative motifs into their artworks while expanding market segmentation. The program employed a Participatory Action Research (PAR) approach through the KUPAR stages (to know, to understand, to plan, to action, and to reflection), implemented through training, mentoring, and evaluation involving 20 painters in Jelekong Village. The results revealed that 90% of participants were able to apply Islamic motifs, including calligraphic, geometric, and floral designs, in their paintings; 80% of participants began utilizing social media as a marketing tool; and 60% successfully developed new products in the form of paintings based on Islamic decorative arts. The program contributed to the enhancement of participants’ skills, product diversification, market expansion, and the strengthening of painters’ competitiveness within a creative economy framework rooted in cultural traditions and Islamic values.